Implication of Education Financing on Student Academic Achievement - Riinawati Riinawati; Fatwiah Noor (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This qualitative research aims to explore the influence of education financing, including scholarship programs and financial aid, on student academic achievement at ULM. The study utilizes in-depth interviews as the primary method for data collection. Students' experiences and perceptions regarding the impact of financial support on their education are gathered through these interviews. Thematic analysis is employed to identify key themes and patterns in the qualitative data. The findings reveal a significant positive correlation between education financing and academic achievement at ULM, as perceived by the students. Students who receive financial assistance through scholarships and aid programs tend to perform better academically, as it alleviates financial burdens and allows them to focus on their studies. These results underscore the pivotal role of education financing in shaping student success at ULM, as perceived by the interviewed students.